2008
DOI: 10.1007/s00253-008-1493-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of morphology on geldanamycin production in submerged fermentations of Streptomyces hygroscopicus var. geldanus

Abstract: The diverse morphology of the filamentous organism Streptomyces hygroscopicus var. geldanus was characterised by image analysis under various environmental conditions. In the presence of surfactant compounds, a significant decrease in the mean pellet diameter was observed. Cell aggregation was also influenced by spore inoculum level, with high concentrations reducing pellet size. In addition, the dispersion of pellets was found to increase with the inclusion of glass beads to submerged shake-flask cultures. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 30 publications
1
37
1
Order By: Relevance
“…A decrease in pellet size with an increase in inoculum level has been previously reported for a Streptomyces sp. for initial spore concentrations in the range 10 2 -10 6 spore/mL (Dobson et al, 2008). For cultures of Streptomyces griseus, Kim and Hancock (2000) reported a similar trend for inoculum concentration in the range 1.5×10 4 to 1.5×10 6 spore/mL.…”
Section: Resultsmentioning
confidence: 70%
“…A decrease in pellet size with an increase in inoculum level has been previously reported for a Streptomyces sp. for initial spore concentrations in the range 10 2 -10 6 spore/mL (Dobson et al, 2008). For cultures of Streptomyces griseus, Kim and Hancock (2000) reported a similar trend for inoculum concentration in the range 1.5×10 4 to 1.5×10 6 spore/mL.…”
Section: Resultsmentioning
confidence: 70%
“…Clumps and dispersed mycelia were found to be the favourable morphology for retamycin production in S. olindensis [190], nystatin production in S. noursei [191], tylosin production in S. fradiae [183], geldamycin production in S. hygroscopicus [192] and the expression of a recombinant Ala-Pro-rich O-glycoprotein in S. lividans [193]. However, productivities were higher in pellets than in dispersive growth forms when producing nikkomycin in S. tendae and avermectin in S. avermitilis, respectively [194,195].…”
Section: Control Of Morphology and Productivitymentioning
confidence: 98%
“…The changes of mycelia morphology of filamentous microorganisms in a biological real-time reaction calorimeter (BioRTCal) have remarkable effect on the primary or secondary metabolites production and enzyme production. It was concluded that the fungal growth in pellet form was a favourable alternative due to advantages such as fungal biomass reuse and improved culture rheology, which resulted in better mass (oxygen) transfer and lower energy consumption (Dobson et al 2008).…”
Section: Introductionmentioning
confidence: 99%